Using quartz fabric intensity parameters to delineate strain patterns across the Himalayan Main Central thrust. (February 2020) - Starnes, Jesslyn K.; Long, Sean P.; Gordon, Stacia M.; Zhang, Jingyi; Soignard, Emmanuel
Abstract: Disagreements over how to define shear zones within packages of pervasively recrystallized rock impede our ability to map and correlate these structures. Here, we explore a new approach for delineating the spatial extents of shear zones using quartz petrofabric, temperature, and kinematic data collected from two transects across the Main Central thrust (MCT) in western Bhutan. We calculated cylindricity, a fabric intensity parameter that has been previously interpreted as a proxy for finite strain magnitude, for each sample. Cylindricity values (measured on a scale from 0 to 1) increase upward from 0.11 to 0.47 between 2.3 and 1.3 km below the MCT, vary between 0.55 and 0.93 between 700 m below and 200 m above the MCT, and decrease upward from 0.68 to 0.37 between 2.4 and 11.7 km above the MCT. Fabric intensity increases with proximity to the MCT and defines a 900 m-thick zone of elevated intensity that overlaps spatially with an interval of inverted metamorphism. Our results add to a growing number of recent studies that suggest that spatial patterns of fabric intensity, when integrated with temperature data and kinematic observations, can be used to delineate relative strain patterns across shear zones in the Himalaya and elsewhere. Highlights: A zone of elevated quartz fabric strength is present across the Main Central thrust. This high intensity fabric zone overlies an interval of inverted metamorphism. The extent of this zone may delineate the boundaries of the Main Central thrust.